PEREMPUAN DAN FEMINISME DALAM PERSPEKTIF ISLAM - Zulfahani Hasyim (MUWAZAH : jurnal kajian gender, 2012)
Women, since the beginning of their creation was equal with men, as God has determined that there is no difference between men and women; and what differs each is only the level of devotion. In Islam, women also have the same rights and obligations as men. They have the rights of the reward of good deeds, and punishment for bad deeds, and have the obligations of the same worship. There are many other areas can be viewed in the concept of Islam as a proof that Islam has put women in the same degree as men and gave many honors. However, on the ongoing development, feminism leads to the irregular liberation for the life of women. This is what ultimately contrary to the concept of equal rights and obligations between men and women in Islam.